Inflammatory bowel disease - Nielsen, Ole Haagen (Henry Stewart Talks, 2016)
Inflammatory bowel disease etiology, IBD epidemiology, IBD diagnosis, Ulcerative colitis, Crohn’s disease, IBD clinical manifestations, IBD therapy